Broad-scale assumptions on available pasture resources and reindeer’s habitat preferences shown to be decoupled from ecological reality of arctic-alpine landscapes - Pape, Roland; Löffler, Jörg (ERDKUNDE, 2016)
Today’s overall challenges of reindeer pastoralism, i.e., pasture degradation, climate change, conflicting land use, and predation as well as the underlying meshwork of ecology, socio-economy, culture, and politics requires further research. Over-utilization of pastures, reinforced by their general loss has led to a decrease in body weight of reindeer, higher mortality, and lower reproduction in parts of Fennoscandia; therefore, this calls for sustainable pasture management based on adapted pasture utilization. This study focuses on different regions in Norway and contributes to current research by implementing and testing a new methodological framework that aims at the joint evaluation of fine-scale spatio-temporal patterns of pasture resources and their actual utilization from a reindeer’s perspective, including an upscaling to spatial entities relevant for management. While we gained valuable insights into the micro-spatial heterogeneity of arctic-alpine ecosystems in terms of pasture resources to be determined by interacting ecological processes and functionalities rather than structures, it were exactly these processes and functionalities that rendered any meaningful upscaling impossible: functionally decoupled from patterns at a broader scale, they could not be derived from the commonly available broad-scale structural data. Hence, approaches that integrate over the micro-spatial variability of arctic-alpine environments along with models that estimate pasture resources must lead to miscalculations of the available resources. Additionally, our findings on habitat preferences, which mirror the available usable resources, point to the fact that organisms experience their environment neither at coarse nor single scales, indicating that any aggregation bias can be significant in projections that do not consider the appropriate scales and inherent functionalities when judging available resources to be utilized. Inaccurately estimated available pasture resources and a utilization of these resources by reindeer that is highly variable in space and time (and thus cannot be described by a single model) have important implications for the management of reindeer pastoralism. Currently, only rough guidelines can be provided; these guidelines need to be combined with the traditional knowledge of the herders to achieve an optimal utilization of the pastures.